Experimental and molecular dynamics simulation of hard asphalt microstructure. (9th May 2023) - Li, Guannan; Chen, Zining; Tan, Yiqiu; Cong, Xinyu; Dong, Yuming; Xiao, Shenqing
Highlights: The short, unordered planar accumulations dominate the asphalt microstructure. The variation coefficient of the density map follows the same trend as the CII values. Saturates have more significant aggregation behavior than asphaltenes. Abstract: To better design and application of hard asphalt, the conventional properties tests, SARA composition experiments, 1 H NMR experiments, and elemental analysis were carried out for five types of hard asphalt and three types of virgin asphalt, and correlation analysis was performed. Systemic molecular dynamics were applied to reveal the microstructure characteristics by producing the density map and the mean square Displacement. The results indicated that the resins component and the number of saturated carbon in the molecular structure are closely related to the high-temperature performance. Meanwhile, the aromatics component and the number of branches connected to the aromatics rings in the molecular system are closely related to the low-temperature performance. Short, unordered planar accumulations dominate the asphalt microstructure. The variation coefficient of the density map follows the same trend as the CII values when characterizing the dispersion ability of the resins and aromatics components. The variation coefficient shows that the saturates components have more significant aggregation behavior than the asphaltenes component. The viscous behavior of asphalt cannot be directly characterized by microstructural distribution but requires further attention to the intermolecular forces within the microstructure.